Hubungan Lama Pemakaian KB Suntik 3 Bulan Dengan Peningkatan Berat Badan Pada Akseptor KB - Dinda Ayu Mira Khusuma; Ni Made Nurtini; Ni Komang Sri Ariani (WOMB Midwifery Journal, 2025)
DMPA/3-month injectable contraceptives are widely used and effective in reducing birth rates. One of the side effects of using 3-month injectable contraceptives is potential weight gain. This study aims to identify the relationship between the duration of use of 3-month injectable contraceptives and weight gain among birth control acceptors. The data analysis method employed the chi-square test, with a sample derived using the Slovin formula from the total population of 108 injectable birth control acceptors, resulting in 52 respondents.The research was conducted at PMB Wipka Yuliana. The measurement tool used was a questionnaire. The findings of this study indicated that the duration of use of three-month injectable birth control for over two years was associated with an increase in weight, with a p-value of 0.001. These results demonstrate a significant relationship between the duration of three-month injectable contraceptive use and weight gain among contraceptive users. There is an association between the duration of three-month injectable contraceptive use and weight gain in birth control users. It is hoped that healthcare workers and recipients of the 3-month injectable contraceptive can find sources of information regarding the side effects associated with the use of DMPA.